Um enfoque bayesiano do modelo de captura-recaptura na presença de covariáveis - Paula, Marcelo de (2006)
This work has as main objective to insert covariates in the capture probability of the multiple capture-recapture method for closed animal population. Factors like climate, seasons of the year, animal size, could a¤ect the animal capture probability. We revise the methodology concepts, we make a study about the posteriori parameters sensibility, we present new parameters for the capture probability in specific situations and we insert covariates in the model used by Castledine (1981) through bayesian methods. The bayesian analysis was made through several studies of stochastic simulation through MCMC (Monte Carlo Markov Chain) with simulated and real data to obtain the population size posteriori results.